Internationalization of Supply Chain of Apparel Industry - G.Pelin Olcay (European Regional Science Association (ERSA), 2016)
This paper is based on the PhD thesis written by the author. Post-fordist production system has raised since 1970's. Main firms have divided production process into different stages and transferred some stages of the production to either other firms in the same factory or another firms in another spaces. Not only production process but also different parts of supply chain have been moved to different geographies. Apparel industry in Turkey has faced with similar development. Large apparel producers have moved some part of their production to the different locations in both Turkey and abroad. The aim of the paper is to investigate which parts of the supply chain of Turkish apparel industry have moved to different geographies and which of those have stayed where it is established. Moreover, it is searched the location and relocation criteria of these firms. A case study has conducted for the research. Eroglu Giyim, one of the biggest apparel supplier of Turkey and owner of very well-known brand of Colin's, and its supply chain have been investigated. Semi-structured deep interviews have been made with Eroglu Giyim, its subcontractors and its input suppliers. Supply and production maps of Eroglu Giyim for the year of 2002 and 2012 have been produced. 27 suppliers of total 35 suppliers have been interviewed to find out their location and re-location criteria. Eroglu Giyim has expanded its production network globally since 2003. The main reasons of this expanding are flexible and international production system, expectations and demands of their customers, legal and trade regulations as well as qualifications and strategies of the firm. Which products to be produced in which geography has been determined by customer demands and expectations. Those are related to some advantages of geography, for example, accessibility, human capital, innovation, proximity and face-to-face contact. Geography of the input supplier of Eroglu Giyim has been mainly shaped by strategies and qualifications of the firm and its suppliers. Legal regulations, which are made by the state in order to restrict the import, causes input to supply from generally Turkey. However, some input are purchased from the foreign international suppliers that make production in Turkey. All these local and international suppliers have mainly concentrated on Marmara Region where Istanbul in. It has observed that Turkish fabric companies have expanded their marketing networks globally for last 10 years. Most of them have a contact office in numerous countries in different continents, especially in Europe. Some of these companies have started to make production abroad. It has been seen obviously in the survey that Turkish fabric suppliers have become international companies for more than 10 years. Geographical proximity still is a very important location criteria for producer firms, suppliers and main customers. Istanbul presents some advantages like transportation, proximity to market, skilled labour force and face-to-face contact for the firms. Especially skilled labour force of Istanbul causes more complicated goods to produce in this city. So, Istanbul still is an important city for the apparel firms although its disadvantages like expensive production cost.
Keywords: R30; 330; Firm Location; Internationalization; Apparel Industry; Flexible Production; Supply Chain; Supply Map